Reversible Data Hiding in Videos for Better Visibility and Minimal Transfer. (2016) - Lakshmi, M.; Arjun, K.P.; Sreenarayanan, N.M.; Arya, K.A.
Abstract: Performing data hiding in videos is very popular now. Video data hiding has large number of applications as it is more secure and also video has high frequency over the internet. When the amount of data to be embedded into the video increases it can adversely affect the quality of the video making it unsuitable for many applications in the area of defence, military, medical, satellite field etc. The important concerns in the area of data hiding in videos are its high visual quality, size of the video stream, the delay that occurs during the network transmission. In the case of MPEG or H.264 videos which are of great visual quality have their size high, so transmission of these videos can be a difficult task even though they are superior in visual quality. Due to the transmission delay, there arise practical problems in using these high quality videos. Among those the most serious issue that the area of data hiding in video face are its poor illumination. Our new method proposes a novel concept where data hiding and the high quality for poor illumination videos are given equal importance. In the proposed method, we are performing contrast enhancement, improving visual quality in the video streams. The noted point is that we are strictly preserving the video file size even after performing contrast enhancement in the videos. The result should always be of better visual quality then only it becomes practically useful.